The prospect directions for claster analysis applied to the tasks and problems of the agricultural production - Sabo, Andrii; Сабо, Андрій Георгійович; Сабо, Андрей Георгиевич; Kashkarov, Anton; Кашкарьов, Антон Олександрович; Кашкарев, Антон Александрович (ФОП Однорог Т. В., 2019)
The cluster analysis can be widely implemented to agriculture for various tasks like machine vision, identification, control and management, FDI, etc. New fields for the cluster analysis application for agriculture are proposed by authors.
Keywords: cluster analysis; agriculture; equipment; machine vision; identification; control and management; FDI; кластерний аналіз; сільське господарство; обладнання; ідентифікація; контроль та управління